Osteoporosis in South-East Asian countries - Thambiah, Subashini C.; Yeap, Swan Sim (Australasian Association for Clinical Biochemistry and Laboratory Medicine, 2020)
Osteoporosis (OP) is a condition where there is low bone density and microarchitectural deterioration which can predispose to fragility fractures. There is a wealth of literature on OP from the developed countries, but less so from Asia. This review will explore the field of OP research in South-East Asia with regard to the epidemiology, the diagnosis of OP and the role of laboratory tests in the management of OP, with emphasis on 25-dihydroxyvitamin D and bone turnover markers.